2016
DOI: 10.1016/j.jspd.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Lumbar Spondylolisthesis Surgery at 2-Year Follow-up

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…They will be used in a separate study to develop evidence-based recommendations for economic evaluations in spine surgery. Finally, a total of 130 clinical cost-effectiveness studies were included 24–153…”
Section: Resultsmentioning
confidence: 99%
“…They will be used in a separate study to develop evidence-based recommendations for economic evaluations in spine surgery. Finally, a total of 130 clinical cost-effectiveness studies were included 24–153…”
Section: Resultsmentioning
confidence: 99%
“…10,41,42 Although those issues have been analyzed by using medical records, the costs varied among societies to obtain a generalized picture of the utilization of medical services. 24,27,[43][44][45][46][47][48] This issue could be addressed by using registered data to reveal the big picture. 21,[24][25][26][27][28][29][30][43][44][45][46][47][48] Recently, claim data have not only been used for accounting but also been used to improve the management of spinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…24,27,[43][44][45][46][47][48] This issue could be addressed by using registered data to reveal the big picture. 21,[24][25][26][27][28][29][30][43][44][45][46][47][48] Recently, claim data have not only been used for accounting but also been used to improve the management of spinal disease. 9,10,20,22,34,[42][43][44][45][49][50][51][52][53][54] National population-based data can be utilized to accomplish goals, such as determining the change in the number of surgical cases, average cost for treatment, use of resources and factors in uencing cost.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several studies have explored the connection between PROMs and cost analysis by calculating QALYs from PROMs. [21][22][23] McAnany et al conducted a study evaluating 5-year costs associated with anterior cervical diskectomy and fusion (ACDF) and cervical disk arthroplasty (CDA) using cost utility values derived from SF-36. 23 From this identified that CDA generated 2.84 QALYs compared with ACDF, which generated 2.1 QALYs, despite costing $17,540 less than ACDF.…”
Section: Patient-reported Outcome Measure Applications In Analysis Of...mentioning
confidence: 99%